Sapphire-bearing magmatic rocks trace the boundary between paleo-continents: a case study of Ilmenogorsky alkaline complex, Uralian collision zone of Russia - Sorokina, Elena S.; Botcharnikov, Roman E.; Kostitsyn, Yuri A.; Rösel, Delia; Häger, Tobias; Rassomakhin, Mikhail A.; Kononkova, Nataliya N.; Somsikova, Alina V.; Berndt, Jasper; Ludwig, Thomas; Medvedeva, Elena V.; Hofmeister, Wolfgang (Gondwana research, 2021)
Metamorphic gem corundum (mainly ruby) deposits are robust indicators of continent-continent collision processes. However, a systematic link of primary magmatic blue sapphire occurrences to orogenic belts is less understood. An example is the Ilmenogorsky alkaline complex, within the Ilmen Mountains region and part of the Uralian orogenic belt. The mobile belt is a product of the collision among Kazakhstania, Laurussia, and Siberia continents prior to the closure of the Paleo-Uralian ocean and formation of the Laurasia supercontinent (330-250 Ma). It is believed that the alkaline complex became inсluded into the separate Sysertsk-Ilmenogorsk microcontinent with unconstrained borders, when sandwiched between Kazakhstania and Laurussia during that collision. Paleo-reconstructions illustrate that magmatic and metasomatic sapphire deposits linked to alkaline magmatism trace the natural boundary of the “lost” microcontinent with a high precision. The syenite pegmatites of alkaline complex carried unusually large corundum-blue sapphire megacrysts that have recorded the multi-stage development of the Ilmenogorsky complex. The deposits were formed at about 275-295 Ma ago as reconstructed by in situ LA-ICP-MS U-Pb zircon dating. This formation stage corresponds to a broader continental collision process followed by the formation of Uralian orogeny in the area of the Ilmenogorsky complex. One pegmatite deposit, the “298” mine, is characterized by the occurrence of unusually large corundum megacrysts. The analyses of Rb-Sr isotopic system in the rocks from this deposit revealed two isochrons at 249 ± 2 Ma and 254 ± 22 Ma implying a late stage modification of original pegmatites. The timing of this stage corresponds to the limited post-collision stretching time. Hence, corundum-blue sapphire studied from magmatic (syenites) and metasomatic rocks linked to alkaline rocks in Uralian orogen suggests as a promising indicator for constraining the timing of continent-to-continent collision processes.
Gesehen am 27.08.2021